(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thepresent study is an attempt to study the environmental awareness of higherprimary school teachers of Warangal City in India. A total of 300 teachers (136 male and 164female) teaching in 6th and 7thstandards were randomly selected for the present study. The environmentalawareness test was employed to assess the level of environmental awareness (EAW)among teachers. Chi-square test and contingency table analysis were employed tofind out the significance of difference between the teachers with respect totheir gender, age and school type. Results revealed that on the whole, majority of the teachers hadmoderate levels of environmental awareness. Female teachers had significantly higher levels of environmentalawareness as compared to their male counterparts. Age-wise analysis also revealed that teacherswith 31-50 years had higher levels of environmental awareness and lastly,teachers working in private schools found to have significantly higherenvironmental awareness than teachers working in government schools.Implications of environmental education were also stressed.